Sustainable fisherman settlement development - Ainun Nurin Sharvina; Muhammad Faqih; Happy Ratna Santosa (Institut Teknologi Sepuluh Nopember, 2017)
Sustainability theory is considered important in the world. The theory has evolved the paradigm of architecture design to the level where it has reconsidering the environment, social and economic. However, the sustainable architecture development plan often implemented from a partial sustainable development theories. This research will discuss the theories of sustainable development that take a place in fisherman settlement area. The fisherman settlement is chosen as the context due to the vulnerability of the area in Indonesia, which showed by the government policy regarding the fisherman settlement. The theoretical study will cover general sustainable development concept to sustainable housing and settlement theories especially in fisherman settlement. This research utilizes a logical and critical argumentation method with descriptive analysis.